2019
DOI: 10.4314/ijbcs.v12i6.17
|View full text |Cite
|
Sign up to set email alerts
|

Détermination de la teneur en résidus de cinq pesticides organochlorés dans le lait des grands bassins laitiers au Mali-Sud

Abstract: pour avoir financé à travers le « Fonds Etude et Recherche » les travaux de cette étude. RESUME Les pesticides organochlorés à cause de leur stabilité chimique persistent et s'accumulent dans différents milieux des régions où ils sont utilisés régulièrement et pénètrent dans la chaîne alimentaire. Leur grande liposolubilité fait qu'ils peuvent être retrouvés dans le lait. La présente étude, réalisée au niveau des zones des grands bassins laitiers au Mali-Sud, vise à déterminer les teneurs en résidus de cinq pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In the article by firmzin on the analysis of water samples from the Couffo River it was revealed that four pesticides were present: glyphosate, profenofos, acetamiprid and cypermethrin. Even glyphosate was detected in all water samples at high levels, above the legal standard recommended for drinking water by the WHO (25). The study in Senegal reveals a worrying contamination of pesticides detected in food products sampled at suburban food markets (30).…”
Section: B) Pesticide Contamination Of Foodmentioning
confidence: 96%
See 1 more Smart Citation
“…In the article by firmzin on the analysis of water samples from the Couffo River it was revealed that four pesticides were present: glyphosate, profenofos, acetamiprid and cypermethrin. Even glyphosate was detected in all water samples at high levels, above the legal standard recommended for drinking water by the WHO (25). The study in Senegal reveals a worrying contamination of pesticides detected in food products sampled at suburban food markets (30).…”
Section: B) Pesticide Contamination Of Foodmentioning
confidence: 96%
“…Another paper in the same area of Sikasso found pesticide residues in market garden produce (24). The study on pesticide analyses in milk from the large dairy basins in southern Mali showed contamination by five organochlorine pesticides (25). Analyses of curdled milk and eggs in Côte d'Ivoire also determined their levels of contamination by organochlorine pesticides (26).…”
Section: B) Pesticide Contamination Of Foodmentioning
confidence: 99%
“…Suppliers who duly comply with all regulatory testing, quality control, and labelling requirements risk losing market share to unregistered products, which incur lower costs by evading regulatory testing, fees, and compliance costs. Consumers of agricultural products face variable—through frequently unquantified—risks from pesticide residues in commonly consumed foods, including vegetables, milk products, and fish (Donkor et al., 2016; Maiga et al., 2018; Theriault et al., 2020). Environmental risks from widespread application of pesticides include possible contamination of water, soils, and animals (Jepson et al., 2014, 2020).…”
Section: Motivationmentioning
confidence: 99%